2019
DOI: 10.1002/mgg3.620
|View full text |Cite
|
Sign up to set email alerts
|

A novel SMAD6 variant in a patient with severely calcified bicuspid aortic valve and thoracic aortic aneurysm

Abstract: Background Bicuspid aortic valve (BAV) is the most common congenital heart defect with a prevalence of 1%–2% in the general population. NOTCH1 , SMAD6 , and GATA5 are associated with BAV in humans, but few cases have been reported that did not involve NOTCH1 . Here, we identified novel in‐frame variants in SMAD6 (c.1168_1173dup; p.Gly390_Ile391dup) in a BAV patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…An enrichment of SMAD6 variants considered to be pathogenic has been reported in several pathologies distinct from CRS. [10][11][12][13][14][15][16][17] Using our variant categorization (based on AF and DS), we evaluated all SMAD6 variants that were previously reported as pathogenic. Systematic review identified 74 different SMAD6 variants, including 30 missense (Table S4, Fig.…”
Section: Re-evaluation Of Smad6 Variants Previously Reported As Pathomentioning
confidence: 99%
See 1 more Smart Citation
“…An enrichment of SMAD6 variants considered to be pathogenic has been reported in several pathologies distinct from CRS. [10][11][12][13][14][15][16][17] Using our variant categorization (based on AF and DS), we evaluated all SMAD6 variants that were previously reported as pathogenic. Systematic review identified 74 different SMAD6 variants, including 30 missense (Table S4, Fig.…”
Section: Re-evaluation Of Smad6 Variants Previously Reported As Pathomentioning
confidence: 99%
“…SMAD6 , originally identified in mammals by homology-based cloning, 5 , 6 encodes one of two (with SMAD7) inhibitory members of the SMAD family required for regulated intracellular signal transduction by members of the transforming growth factor β/bone morphogenetic protein (TGFβ/BMP) superfamily. 7 9 Intriguingly, enrichment of rare SMAD6 variants has also been reported in association with several other distinct phenotypes, namely congenital heart disease, 10 12 bicuspid aortic valve (BAV) and ascending thoracic aortic aneurysm (TAA), 13 15 intellectual disability, 16 and radioulnar synostosis. 17 …”
Section: Introductionmentioning
confidence: 99%
“…Loss-of-function SMAD6 variants have been variably associated with different clinical phenotypes, including cardiac, craniosynostosis and RUS, in the absence of any strict genotype-phenotype correlation. Among the cardiac features, an association between BAV/aortic coartaction and SMAD6 haploinsufficiency has been established [ 16 , 17 , 18 , 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…Enrichment of rare/private truncating and MH1/MH2-domain missense variants in SMAD6 has been reported in association with a wide spectrum of congenital heart defects (CHD). These defects include tetralogy of Fallot (TOF), hypoplastic left heart syndrome, aortic coarctation (CoA) and D-transposition of great arteries (D-TGA), aortic valve disease (AVD, MIM: 614823) with variable degrees of aortic calcifications [ 14 , 15 , 16 , 17 , 18 , 19 ]. These variants have also been associated with susceptibility to craniosynostosis (MIM: 617439) [ 20 , 21 ], and non-syndromic radioulnar synostosis (RUS, MIM: 179300) [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The SMAD6 gene variation is associated with thoracic aortic aneurysm in patients with non-syndrome BAV (Galvin et al, 2000;Gillis et al, 2017;Luyckx et al, 2019). However, only a few of the SMAD6 variants presented as BAV were accompanied by thoracic aortic aneurysm, while most of the variants presented variable clinical phenotypes (Luyckx et al, 2019;Park et al, 2019). NOTCH1 has been identified as a candidate gene associated with BAV.…”
Section: Pathophysiology Genetic Predispositionmentioning
confidence: 99%